Factors influencing quality of life in cancer patients receiving haemodialysis - Atilgan, Kadir Gokhan; Ayli, Mehmet Deniz; Eren, Tulay; Karacin, Cengiz; Sahin, Hatice; Selen, Tamer; Gok Oguz, Ebru; Ayerden Ebinc, Fatma; Ulusal Okyay, Gulay (Progress in Nutrition, 2020)
Background: Life expectancy in cancer patients is shorter than in the general population. Therefore quality of life is important. The quality of life and the affecting factors in cancer patients receiving haemodialysis (HD) treatment are not clearly known. Objective: This study evaluated factors affecting quality of life in cancer patients undergoing HD compared to patients without cancer undergoing HD. Methods: The study was conducted between May 2019 and September 2019. The dialysis unit of the authors’ hospital and ten private HD centres participated in the present case control study. The study included 37 cancer patients undergoing HD (Group CA) and age, sex matched 37 patients undergoing HD without cancer (Group C). Quality of life was assessed with the health-related quality of life short form-36. Muscle mass and malnutrition were evaluated with the hand grip strength (HGS) test and malnutrition-inflammation score (MIS). Sleep disorder was assessed using the Pittsburgh sleep quality index (PSQI). Results: In Group CA, HGS was significantly related to both mental composite scores and mental health (p = 0.023, r = 0.374; p < 0.001, r = 0.519, respectively). In Group C, a significant relationship was detected between HGS and both physical composite scores and general health (p = 0.03, r = 0.356; p = 0.017, r = 0.397, respectively), between the PSQI and physical role functioning (p = 0.03, r = -0.336) and between the MIS and HGS (p = 0.012, r = -0.408). Conclusion: Only HGS affected quality of life in cancer patients undergoing receiving HD treatment.